AN ANALYSIS OF MORAL VALUES IN “ZOOTOPIA” MOVIE DIRECTED BY BYRON HOWARD AND RICH MOORE - Mukhlasul Fasikh; Demici Natali (STIBA IEC JAKARTA, 2021)
This thesis attempts to analyze in the movie Zootopia directed by Byron Howard and Rich Moore. The study is based on two research questions, first about kind of moral values and second about the effects of moral values through the main character. The methodology of the study is descriptive qualitative. It means that it does not need statistic approach to explore the material. The primary data is taken from the original movie itself and script from Zootopia movie. The secondary data is taken from many journals, literary books and some relevant materials to support and complete the primary data sources. The result shows that there are ten types of kind of moral values which the writers found by in the script of the movie Zootopia. They are brave, respect, kind and friendly, confidence, loyalty, self-discipline, fair and human, love and affection, honesty and sensitive and not selfish. Then, the effects of moral values that reflected through the main character are optimistic, brave, ambitious, caring, and enthusiastic. The writers hope that movie lovers can see the positive aspect and take it to imply their life